Effect of simultaneous application of arthrocentesis and occlusal splint versus splint in management of non-reducing TMJ disc displacement - Alaa Abdelqader Altaweel; Hussein Abdelfattah Ismail; Mostafa I. Fayad (Elsevier, 2021)
Background/Purpose: This study aimed to compare the effect of four approaches in the treatment of TMJ disc displacement without reduction (DDwoR). Materials and methods: Thirty-two patients (40 joints) with mean age 28.025 ± 7.18 (23 female patients and nine male patients) were assigned randomly into four groups (10 joints in each group). Group I, patients were treated by centric splint. Group II, patients were treated by distraction splint. Group III, patients were treated by arthrocentesis and centric splint, while group IV patients were treated by arthrocentesis and distraction splint. The groups were compared in terms of joint function (mouth opening), joint pain through joint palpation, and use of visual analog scale (VAS). These records were taken preoperatively, two weeks, one month, three, and six months postoperatively. Also, the presence of disc recapture was evaluated in all patients on MRI at the end of the treatment period. Results: Significant improvements in all parameters were recorded in all groups. At two weeks postoperatively, there was a significant improvement in all parameters in group III and group IV than group I and group II, while there was no statistical difference between group III and group IV. Regarding mouth opening and joint palpation, there was a significant improvement in group III than group I and group II. Also, there was a significant improvement in group IV than group II at the subsequent follow-up periods. Regarding VAS, at one and three months postoperatively, there was a significant improvement in group III than other groups. Conclusion: However, both types of splints provide better results without a statistical difference; the simultaneous application of arthrocentesis and occlusal splint decreases pain and improving the function effectively and more rapidly.